(untitled) (Scientific journal of the Fergana State University, 2023)
This article analyzes the present and future days of happiness, the further development of religious and secular views of the future generations, the understanding of intellectual, empirical and emotional intelligence, the relationship of idealism in life, family happiness in social relationships, intellectual and spiritual potential, not only knowing the world, but also scientific knowledge of factors of raising the ethical culture of young people.